Epithelial to Mesenchymal Transition: Key Regulator of Pancreatic Ductal Adenocarcinoma Progression and Chemoresistance - Kostas Palamaris (MDPI AG, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest malignancies, characterized by aggressive biological behavior and a lack of response to currently available chemotherapy. Emerging evidence has identified epithelial to mesenchymal transition (EMT) as a key driver of PDAC progression and a central regulator in the development of drug resistance. EMT is a reversible transdifferentiation process controlled by complex interactions between multiple signaling pathways such as TGFb, Wnt, and Notch, which converge to a network of specific transcription factors. Activation of EMT transcriptional reprogramming converts cancer cells of epithelial differentiation into a more mesenchymal phenotypic state. EMT occurrence in pre-invasive pancreatic lesions has been implicated in early PDAC dissemination. Moreover, cancer cell phenotypic plasticity driven by EMT contributes to intratumoral heterogeneity and drug tolerance and is mechanistically associated with the emergence of cells exhibiting cancer stem cells (CSCs) phenotype. In this review we summarize the available data on the signaling cascades regulating EMT and the molecular isnteractions between pancreatic cancer and stromal cells that activate them. In addition, we provide a link between EMT, tumor progression, and chemoresistance in PDAC.